1970
DOI: 10.1159/000179825
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Total Body, Serum and Erythrocyte Potassium in Patients on Maintenance Haemodialysis. The Value of Erythrocyte Potassium as a Measure of Body Potassium

Abstract: Total body, Erythrocyte and Serum potassium changes during haemodialysis were studied on 29 occasions in 15 patients on maintenance dialysis with a low dialysate potassium concentration (1 mEq/l). The loss in total body potassium during haemodialysis (measured with a whole body counter) varied widely and was significantly related to the pre-dialysis body potassium state of the patient as assessed by total body potassium per kg body weight in spite of a constant high serum to dialysate concentration gradient in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
2
2

Year Published

1971
1971
1991
1991

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 3 publications
0
5
2
2
Order By: Relevance
“…This conclusion contrasts with previous findings (Johny et al, 1970) which showed that a decrease in erythrocyte K+ correlated well with a decrease in total body K+ during haemodialysis. It is very likely that serial determinations of erythrocyte K+ are useful for detecting changes in total body K+.…”
Section: Discussioncontrasting
confidence: 99%
“…This conclusion contrasts with previous findings (Johny et al, 1970) which showed that a decrease in erythrocyte K+ correlated well with a decrease in total body K+ during haemodialysis. It is very likely that serial determinations of erythrocyte K+ are useful for detecting changes in total body K+.…”
Section: Discussioncontrasting
confidence: 99%
“…Such a modest diminution in intracellular potassium concentration is unlikely to be associated with significant structural or metabolic abnormality [4,5]. Although a number of reports compare groups of subjects in terms of TBK/body weight [18][19][20][21] and TBK/FFWt [22], it would seem more desirable to consider TBK in terms of ICV as described by Rettori et al [1]. The decline in intracellular potassium concentration of 7.1% during dialysis was accompanied by a decline in Ks of 40.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Ce dernier est influencé, chez les insuffisants rénaux, par de multiples facteurs agissant dans des sens divers: équilibre acide-base, défaut d'élimina tion, restriedons diététiques, etc. On ne dispose encore que de peu d'informations sur le capital potassique des insuffisants rénaux et l'effet que l'hémodialyse exerce à son niveau, et les résultats publiés ne sont pas univoques [11,12]. L'introduction de la mesure du potassium total des patients par «compteur corporel total » (whole body counter) en milieu hospitalier a cependant permis d'aborder cette étude avec une facilité relative.…”
Section: Introductionunclassified
“…Nos résultats concordent avec les constatations récentes de J o h n y et al [11], tant en ce qui concerne l'importance quantitative de ces pertes que leurs corrélations avec les valeurs initiales de potassium cor porel; par contre, M o r g a n et al [12] ne considèrent pas la perte de potassium comme significative, dans des conditions il est vrai légè rement différentes des nôtres. La perte de potassium est certes inéga lement répartie selon les individus et les séances de dialyse, et dans certains cas on constate même un léger gain.…”
unclassified